Titanium dioxide: A heterogeneous catalyst for dark peroxidation superior to iron oxide. Issue 5 (October 2020) - Fernández-Pérez, Amparo; Marbán, Gregorio
Abstract: In this work, high specific surface area stainless steel wire mesh-supported TiO2 catalysts (SSWM-TiO2 ) were synthesized by a modification of the sacrificial polar template accelerated hydrolysis method that permits over 98 mol% purity to be attained. The TiO2 catalysts show an excellent activity in the heterogeneous peroxidation of aqueous methylene blue (MB) in the dark, with clear superiority over Degussa P25® powders or even over the highly active Fe2 O3 particles. With the results of batch reaction experiments and the physicochemical characterization of the catalysts, a new reaction mechanism was proposed. This considers the adsorption of H2 O2 on an acid site of the catalyst that then forms a hydroperoxyl-Ti activated complex with the help of a nearby Ti 4+ −OH center (two-site H2 O2 activation). MB reacts from the solution with the activated complex following an Eley-Rideal mechanism. A kinetic analysis with the best performing catalyst, TiO2 calcined at 350 °C, resulted in a new kinetic model equation for the proposed reaction mechanism. The increase of the acid sites fraction on increasing the catalyst dosage and the deactivation rate due to adsorption of aromatic reaction intermediates on the acid sites were also included in the kinetic equation. A flow-through reactor was tested with the structured catalysts for continuous flow mode operation. The SSWM-TiO2 catalysts showed high activity and stability under the different reaction conditions, with a slight deactivation degree after long reaction periods, though the activity was restored after a simple regeneration step with H2 O2 /water mixture under solar light irradiation.